2021
DOI: 10.4025/ciencuidsaude.v20i0.56189
|View full text |Cite
|
Sign up to set email alerts
|

Fluxos de atendimento em um centro obstétrico frente à pandemia da covid-19: relato de experiência/Flows of care in an obstetric center in the face of the covid-19 pandemic: experience report

Abstract: Objetivo: relatar o desenvolvimento e implementação de fluxos para atendimento de gestantes com suspeita ou confirmação de COVID-19 no Centro Obstétrico de um hospital público. Método: estudo descritivo, do tipo relato de experiência, realizado em um hospital público de Porto Alegre/RS, referência para atendimento de gestantes com COVID-19. Resultados: descreveram-se fluxos para atendimento à gestante com suspeita ou confirmação de COVID-19 nas seguintes situações: acolhimento e classificação de risco em obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Since the pre-pandemic period, prenatal care had already been difficult for pregnant women to adhere to and, in the face of COVID-19, this scenario has worsened 23 . In view of this, it is of great importance to institute actions aimed at adherence to care, especially in the group of pregnant women, given the relevance of this strategy for the prevention, detection and treatment of health conditions that affect the dyad.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pre-pandemic period, prenatal care had already been difficult for pregnant women to adhere to and, in the face of COVID-19, this scenario has worsened 23 . In view of this, it is of great importance to institute actions aimed at adherence to care, especially in the group of pregnant women, given the relevance of this strategy for the prevention, detection and treatment of health conditions that affect the dyad.…”
Section: Discussionmentioning
confidence: 99%
“…25,28,29 Prenatal care was also impacted by a reduction in the number of pregnant women seen, a reduction in the number of appointments and many reported that when they were seen, they were not allowed to be with a companion, in order to avoid crowding and the spread of the virus, and collective and group appointments had to be suspended. 26,[30][31][32][33] The absence of pregnant women's groups limits the process of health education that can be positive in terms of preparation and empowerment about pregnancy, childbirth and breastfeeding, which has a direct impact on the well-being of these mothers, as well as on the care of their newborn, leaving them more alone to face this moment. 34 In this sense, there is a gap involving the lack of these collective groups, which have a direct influence on pregnant women coping with their current pregnancy.…”
Section: Vulnerabilities and Impacts For Women In The Pregnancy Cycle...mentioning
confidence: 99%